50 Human Brain Ideas You Really Need to Know - Moheb Costandi (Quercus, 2013)
Neuroscience is one of the most fascinating and complex areas of scientific research, with new advances being made every day. In 50 Human Brain Ideas You Really Need to Know, Mo Costandi condenses all we know about the brain and how it works into series of introductions to the most important concepts. Outlining both long-standing theories - such as the function of neurons and synaptic transmission - and cutting-edge ideas - including neuroethics and brain-computer interfacing - with straightforward narrative and clear two-colour illustrations, this book is a perfect beginner\\\\\\\'s guide to the most powerful and mysterious organ in the body. The ideas explored include: The nervous impulse; Differences between the male and female brain; The root of addiction; Neurobiological basis for personality; The relationship between sleep and memory.